CORRESPONDENCE BETWEEN MODELS AND FACTORS OF STUDENT ERRORS IN SOLVING CONTEXTUAL PROBLEMS - Fiki Alghadari; Audi Yundayani; Abdul Halim Abdullah (Aksioma: Jurnal Program Studi Pendidikan Matematika, 2022)
The acquisition of knowledge assists students in navigating life, but their skill configuration is unstable when confronted with contextual problems. The fact that they make problem-solving errors is a stability problem that stems from existential situations. This study examined students' errors in solving contextual math word problems. The respondents were 36 Jakarta junior high school students. This work employs an existential design informed by phenomenology to lessen the connection between the model and error-causing. Newman's strategy found various types of errors. The researchers then investigated the error model and the root causes of the detected errors through interviews. According to the ontological investigation, seven correspondences were discovered between the error models and the causative factors, namely comprehension, transformation, and process skills, so that the origin of occurrences remained unchanged. Deficiencies in process skills cause the majority of correspondence. The phenomenological reduction of the correspondence demonstrates that students are not always engaged in higher-order thinking and tend to concentrate on the procedural knowledge learning process. It can be concluded that the learning process must encourage students' higher-order thinking. When students learn and gain experience through misunderstandings and transformations, they will demonstrate constructive efforts and computational thinking by troubleshooting the problem-solving strategy.